USABILITY EVALUATION ON THE NEW STUDENT ADMISSIONS SYSTEM USING THE HEURISTIC EVALUATION METHOD - nurhaliza azzini; Idria Maita; Tengku Khairil Ahsyar; Fitriani Muttakin; Siti Monalisa; Arif Marsal (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The Dumai College of Technology (STT) has implemented a New Student Admission System for prospective students to register online. Based on the results of interviews with the SPMB manager, during its implementation there has never been a usability evaluation. So that the SPMB manager does not know what user needs or problems experienced by system users are. Therefore, researchers conducted usability research. The purpose of this study is to measure the success rate of the New Student Admission System by using the Heuristic Evaluation method so that it can provide recommendations to the manager of the New Student Admission System for future system improvements to meet user needs. The results of the research questionnaire there are 93 data respondents who use SPMB. Based on the results of the usability evaluation on the STT Dumai New Student Admission System, it was found that the total percentage of respondents was found to be 65.2% which can be said that the SPMB STT Dumai was "Good", while the results of the total percentage of respondents were not found, namely 34.8% which can be said to be "Not Good" for the SPMB STT Dumai. ” for system users. From the usability results found 4 statements that get the lowest percentage value which means it is not successful and needs to be improved. The results of the recommendations obtained in the SPMB can be used as an illustration for improvement.